2018
DOI: 10.1515/hsz-2018-0327
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and antioxidants in the pathophysiology of malignant melanoma

Abstract: Oxidative stress and antioxidants in the pathophysiology of malignant melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 225 publications
(235 reference statements)
2
82
0
Order By: Relevance
“…Melanoma cells exhibited significantly higher oxidative stress and produced larger amounts of ROS when compared to melanocytes and surrounding normal tissue [107]. ROS stimulated melanoma progression and metastatization through a number of changes, including (i) DNA modification, (ii) cell proliferation, (iii) tissue remodeling, (iv) immune surveillance escape, (v) pro-metastatic processes activation [108,109]. Malorni and colleagues demonstrated that males express lower levels of anti-oxidants, such as glutathione (GSH), catalase and superoxide dismutase (SOD) when compared to females, thus exhibiting a higher rate of oxidative stress [110,111].…”
Section: Sex and Immunitymentioning
confidence: 99%
“…Melanoma cells exhibited significantly higher oxidative stress and produced larger amounts of ROS when compared to melanocytes and surrounding normal tissue [107]. ROS stimulated melanoma progression and metastatization through a number of changes, including (i) DNA modification, (ii) cell proliferation, (iii) tissue remodeling, (iv) immune surveillance escape, (v) pro-metastatic processes activation [108,109]. Malorni and colleagues demonstrated that males express lower levels of anti-oxidants, such as glutathione (GSH), catalase and superoxide dismutase (SOD) when compared to females, thus exhibiting a higher rate of oxidative stress [110,111].…”
Section: Sex and Immunitymentioning
confidence: 99%
“…Oxidative stress has been considered as a major contributor to the development of skin cancers, such as melanoma [144][145][146]. Accordingly, antioxidants, including resveratrol, have been used to prevent and treat skin cancer [147][148][149], although exacerbation and increased risk of cancers have been reported [150,151].…”
Section: Anticancermentioning
confidence: 99%
“…Oxidative stress and intracellular redox state balance are essential. Evidence also shows that high intracellular ROS levels could cause an increase in antioxidant enzymes for compensation and homeostasis balance [7,[21][22][23]. Based on our previous findings that antioxidants, such as SOD2 and peroxiredoxin-1 (PRDX1), are elevated in dabrafenib resistant (DR) melanoma cells identified from a proteomics screen [7], we aimed to assess SOD2 and PRDX1 levels in BRAF and MEK inhibitor-resistant cells.…”
Section: Sod2 and Nf-κb Levels Are Increased In Braf Pathway Inhibitomentioning
confidence: 99%